Reducing the use of benzodiazepines and cyclopyrrolones in clinical practice - Jørgensen VR; Toft BS; Fogh MS (Centro de Investigaciones y Publicaciones Farmaceuticas, 2006)
Objective: Recently, the use of benzodiazepines (BZD) and cyclopyrrolones (CP) has drawn a great deal of attention. About 100,000 patients - approximately 2% of the Danish population - are believed to be addicted to BZD. This article describes a simple and effective method of reducing the use of dependency-producing drugs in clinical practice. Methods: Design: Local rules were implemented according to Danish directive CIR nr 12 13/01/2003 regarding addictive drugs. Prescriptions for BZD and CP were only issued on a monthly basis, and only following personal consultation. This monthly requirement forced the physician as well as the patient to evaluate whether the existing prescription pattern was indicated, or whether a drug-reducing regime should be introduced. The prescription pattern was monitored using the Ordiprax System (Institute for Rational Pharmacotherapy, IRF), which records pharmacy's sales of prescription drugs as prescribed by clinical practices. Two individual clinics in Thyborøn - Harboøre Community, covering some 2300 patients, were surveyed. All patients using BZD or CP were included in this study, with the exception of patients suffering from serious psychiatric or physical disorders. Results: After 15 months, the use of BZD and CP was reduced by 50% and 75%, respectively. The process of changing prescription habits was far easier than expected. A whole group of patients, initially invisible to the physician, was exposed. During the first three months, as few as 4-5 additional consultations for every 1000 patients was required. There was essentially no need for assistance from our usual partners, including psychiatrists, hospitals, specialist units for addictive treatment. Conclusion: We strongly recommend that these simple procedures be incorporated into daily routine when prescribing either a BD or a CP.